Azole Antifungals Under Pressure: Therapeutic Challenges and Multifaceted Resistance Mechanisms - Santos, André L.S.; Ramos, Lívia S.; Mello, Thaís P.; Viganor, Livia; Nonato, Noely M.B.M.; Pinheiro, Raizza E.E.; Branquinha, Marta H. (Current Medicinal Chemistry, 2025)
Fungal infections have increased markedly in both incidence and severity over recent decades, driven in part by the emergence of novel pathogenic species harboring sophisticated resistance mechanisms against commonly used antifungal agents. This alarming trend is especially pronounced with azoles, which remain widely used in clinical settings due to their broad-spectrum activity and favorable oral bioavailability. Azoles exert their antifungal effect by inhibiting lanosterol 14α-demethylase, a key enzyme in the ergosterol biosynthesis pathway, thereby compromising the integrity, fluidity, and functionality of the fungal cell membrane. However, the escalating prevalence of multidrug-resistant fungal strains, particularly those resistant to azoles, has significantly complicated therapeutic strategies and represents a growing threat to global public health. This perspective explores the diverse and increasingly complex mechanisms of azole resistance in clinically relevant fungi, particularly species of <span class=
Keywords: Candida